Night's illusion - Ashley, Amanda (Zebra paranormal romance., 2021)
Giovanni Lanzoni, the oldest male virgin vampire who has clung to the vows he made a thousand years ago as a mortal priest, risks everything when he finds his perfect mate on a dark night.